Visual search behaviour and information extraction differences between high-level and developing swimming coaches - Waters, A.; Brendan, L.; Tidman, S.; Benjanuvatra, N. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
In swimming, where developing efficient technique is integral to achieving the main goal of swimming faster [1], a coach's ability to diagnose the strengths and weaknesses of an athlete's performance is critical for optimal development of the athlete. This relies on having a high-level of perceptualcognitive skill that enables coaches to integrate visual information with existing knowledge ensuring the right decision concerning a swimmer's technique can be made. A critical element of this is knowing where and when to look while observing a performance [2). Despite this, information pertaining to the understanding of visual perceptual skills in swimming coaching is limited and it is unclear whether expert swimming coaches have developed visual search strategies that enable them to be more efficient at the way they extract and use visual information. While the visual perceptual skill of an athlete has been shown to be an indicator of expertise evidence supporting the idea of an expert coach also having superior visual perceptual skills is inconclusive. Recording of the coach's eye movements while watching a performance enables a direct evaluation of what aspects of the performance the coach is looking at. The location of a gaze fixation identifies an area of interest and the number and duration of fixations reflects the amount of information processed [3]. Of the limited research, however, the results are varied and a common visual search characteristic could not be established for expert coaches across a variety of sports. Some studies have found that expert coaches display a smaller number of fixations of longer duration [4, 5), while others have found no differences between expertise groups [6, 7). In swimming, Moreno, Saavedra, Sabido and Luis [8) found no differences in the number, location or duration of fixations between swimming coaches of high and low levels of experience. lt is important to recognise that the limitation associated with relying on visual fixation data alone. Essentially, the studies mentioned above only reported what the subjects were looking at, and not what information was extracted from the visual environment. Without this information, it is not possible to critically assess the significance of the visual search behaviours of the coaches. Given that accumulation and organisation of knowledge specific to their field is a component that underpins an expert's performance [9), and experts are able to represent problems in terms of their theoretical foundations whereas non-expert's only view a problem's surface aspects [10], it is logical that visual search behaviour would be influenced by the amount of knowledge and experience one has. How this relationship works, however, remains inconclusive and warrants further investigation. Therefore, this study sought to investigate whether expert coaches with greater than 10 years of experience would have a different visual search strategy that enable them to extract greater amount of technical information when viewing a short video clip of a swimmer performing a freestyle sprint. More specifically, this study hypothesised that expert coaches will be able to extract a larger amount of information of greater depth than their developing counterparts, and would be more accurate at predicting the swimmers' ability (swim time) than developing coaches. They would achieve this by relying on fewer gaze fixations that are of longer durations than that of developing counterparts.